السمات الكرافيكية في اللوحة التشكيلية المعاصرة في كوردستان العراق - فخری, مدرس مساعد هاوری أنور (Sulaimani Journal for Humanities, 2021)
This research concerns with examining (the graphic features of the modern fine art painting in Kurdistan of Iraq), and it consists of four chapters. The first chapter concerns in displaying the research problem, importance and objectives of the study, and the limitations, in which confined to reveal the graphic features of the modern fine art painting of the Kurdish artists in Sulaimaniyah City within the period of 1995 to 2005. It also addresses some terms included in this study in terms of language and terminology and defines them procedurally. The second chapter that designed as a theoretical framework includes three topics. The first topic gives a brief summary of the history of graphic art in the world by addressing the way of how the graphic art and its technics have been emerged worldwide throughout its developing stages, and the artists who worked in this field over different eras. The second topic concerns with the history of the graphic art in Kurdistan of Iraq, and highlighting its emergence and movements. While the third topic addressed a group of artistic and technical features that used in graphic art through a number of various typography methods. The Third Chapter represents the research methodology and its procedures including, methodology, in that the researcher depends on analyzing the samples (Descriptive Analysis) method, that started by collecting the art works and ending with what have been analyzed as a sample resulted in outcomes that answered the study objectives directly. Theses answers have been displayed along with the recommendations in the fourth chapter. The results show that all the samples have employed the graphic features such as (the linear, chromatic, formative, and technical features), each according to its style and its expressive potential.